A should be the right answer because 4*5/4=5 + 5*2=10 and 5+10=15.
The 6 people each got
. To get this answer you need to divide the
of the cake among 6 people.
Equation ⇒
x ![\frac{1}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B6%7D)
You get the answer by multiplying the bottom denominators.
Answer:
18 times
Step-by-step explanation:
Sample space ; roll of 2 number cubes = 6^2 = 36
Sum of 4 in 2 cube rolls = 3
Probability = required outcome / Total possible outcomes
P(sum of 4) = 3 / 36 = 1 / 12
If number cube is rolled 216 times :
Probability on 1 roll * Number of rolls
(1 / 12) * 216
0.0833333 * 216
= 18
1. I suppose the ODE is supposed to be
![\mathrm dt\dfrac{y+y^{1/2}}{1-t}=\mathrm dy(t+1)](https://tex.z-dn.net/?f=%5Cmathrm%20dt%5Cdfrac%7By%2By%5E%7B1%2F2%7D%7D%7B1-t%7D%3D%5Cmathrm%20dy%28t%2B1%29)
Solving for
gives
![\dfrac{\mathrm dy}{\mathrm dt}=\dfrac{y+y^{1/2}}{1-t^2}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dt%7D%3D%5Cdfrac%7By%2By%5E%7B1%2F2%7D%7D%7B1-t%5E2%7D)
which is undefined when
. The interval of validity depends on what your initial value is. In this case, it's
, so the largest interval on which a solution can exist is
.
2. Separating the variables gives
![\dfrac{\mathrm dy}{y+y^{1/2}}=\dfrac{\mathrm dt}{1-t^2}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Cmathrm%20dy%7D%7By%2By%5E%7B1%2F2%7D%7D%3D%5Cdfrac%7B%5Cmathrm%20dt%7D%7B1-t%5E2%7D)
Integrate both sides. On the left, we have
![\displaystyle\int\frac{\mathrm dy}{y^{1/2}(y^{1/2}+1)}=2\int\frac{\mathrm dz}{z+1}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cint%5Cfrac%7B%5Cmathrm%20dy%7D%7By%5E%7B1%2F2%7D%28y%5E%7B1%2F2%7D%2B1%29%7D%3D2%5Cint%5Cfrac%7B%5Cmathrm%20dz%7D%7Bz%2B1%7D)
where we substituted
- or
- and
- or
.
![\displaystyle\int\frac{\mathrm dy}{y^{1/2}(y^{1/2}+1)}=2\ln|z+1|=2\ln(y^{1/2}+1)](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cint%5Cfrac%7B%5Cmathrm%20dy%7D%7By%5E%7B1%2F2%7D%28y%5E%7B1%2F2%7D%2B1%29%7D%3D2%5Cln%7Cz%2B1%7C%3D2%5Cln%28y%5E%7B1%2F2%7D%2B1%29)
On the right, we have
![\dfrac1{1-t^2}=\dfrac12\left(\dfrac1{1-t}+\dfrac1{1+t}\right)](https://tex.z-dn.net/?f=%5Cdfrac1%7B1-t%5E2%7D%3D%5Cdfrac12%5Cleft%28%5Cdfrac1%7B1-t%7D%2B%5Cdfrac1%7B1%2Bt%7D%5Cright%29)
![\displaystyle\int\frac{\mathrm dt}{1-t^2}=\dfrac12(\ln|1-t|+\ln|1+t|)+C=\ln(1-t^2)^{1/2}+C](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Cint%5Cfrac%7B%5Cmathrm%20dt%7D%7B1-t%5E2%7D%3D%5Cdfrac12%28%5Cln%7C1-t%7C%2B%5Cln%7C1%2Bt%7C%29%2BC%3D%5Cln%281-t%5E2%29%5E%7B1%2F2%7D%2BC)
So
![2\ln(y^{1/2}+1)=\ln(1-t^2)^{1/2}+C](https://tex.z-dn.net/?f=2%5Cln%28y%5E%7B1%2F2%7D%2B1%29%3D%5Cln%281-t%5E2%29%5E%7B1%2F2%7D%2BC)
![\ln(y^{1/2}+1)=\dfrac12\ln(1-t^2)^{1/2}+C](https://tex.z-dn.net/?f=%5Cln%28y%5E%7B1%2F2%7D%2B1%29%3D%5Cdfrac12%5Cln%281-t%5E2%29%5E%7B1%2F2%7D%2BC)
![y^{1/2}+1=e^{\ln(1-t^2)^{1/4}+C}](https://tex.z-dn.net/?f=y%5E%7B1%2F2%7D%2B1%3De%5E%7B%5Cln%281-t%5E2%29%5E%7B1%2F4%7D%2BC%7D)
![y^{1/2}=C(1-t^2)^{1/4}-1](https://tex.z-dn.net/?f=y%5E%7B1%2F2%7D%3DC%281-t%5E2%29%5E%7B1%2F4%7D-1)
I'll leave the solution in this form for now to make solving for
easier. Given that
, we get
![1^{1/2}=C\left(1-\left(-\dfrac12\right)^2\right))^{1/4}-1](https://tex.z-dn.net/?f=1%5E%7B1%2F2%7D%3DC%5Cleft%281-%5Cleft%28-%5Cdfrac12%5Cright%29%5E2%5Cright%29%29%5E%7B1%2F4%7D-1)
![2=C\left(\dfrac54\right)^{1/4}](https://tex.z-dn.net/?f=2%3DC%5Cleft%28%5Cdfrac54%5Cright%29%5E%7B1%2F4%7D)
![C=2\left(\dfrac45\right)^{1/4}](https://tex.z-dn.net/?f=C%3D2%5Cleft%28%5Cdfrac45%5Cright%29%5E%7B1%2F4%7D)
and so our solution is
![\boxed{y(t)=\left(2\left(\dfrac45-\dfrac45t^2\right)^{1/4}-1\right)^2}](https://tex.z-dn.net/?f=%5Cboxed%7By%28t%29%3D%5Cleft%282%5Cleft%28%5Cdfrac45-%5Cdfrac45t%5E2%5Cright%29%5E%7B1%2F4%7D-1%5Cright%29%5E2%7D)